Composition for polishing

The polishing composition, which includes water, abrasive grains, a composite metal oxide, and an anionic polymer, addresses the challenge of achieving high polishing speed while minimizing friction on high-hardness materials, thereby reducing defects and improving manufacturing efficiency.

JP7667079B2Active Publication Date: 2025-04-22FUJIMI INCORPORATED
View PDF 13 Cites 0 Cited by

Patent Information

Application Number
JP2021528216
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2019-06-17
Filing Date
2020-06-15
Publication Date
2025-04-22
Estimated Expiration
2040-06-15

AI Technical Summary

Technical Problem

Existing polishing compositions face challenges in achieving high polishing speed while minimizing friction, particularly when polishing high-hardness materials like silicon carbide, which can lead to defects and distortions.

Method used

A polishing composition comprising water, abrasive grains (such as alumina or silica), and a composite metal oxide as an oxidant, combined with an anionic polymer to reduce friction and maintain high polishing speed.

Benefits of technology

The proposed composition effectively reduces friction against the object being polished, allowing for improved polishing speed and reduced occurrence of defects like scratches and dents, even under severe polishing conditions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007667079000001
    Figure 0007667079000001
  • Figure 0007667079000002
    Figure 0007667079000002
  • Figure 0007667079000003
    Figure 0007667079000003
Patent Text Reader

Abstract

A polishing composition is provided with which a work can be polished with reduced force of friction therewith at a satisfactory polishing rate. The polishing composition provided by the present invention comprises water, abrasive grains, and a composite metal oxide as an oxidizing agent. The polishing composition further contains an anionic polymer. Some preferred embodiments of the polishing composition contain a permanganate as the composite metal oxide. The polishing composition is suitable for use in polishing materials having Vickers hardnesses of 1,500 Hv or higher.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a polishing composition. More specifically, the present invention relates to a polishing composition used for polishing an object to be polished. This application claims priority based on Japanese Patent Application No. 2019-112283 filed on June 17, 2019, the entire contents of which are incorporated herein by reference. [Background technology]

[0002] Conventionally, polishing using a polishing composition has been performed on the surfaces of materials such as metals, semimetals, nonmetals, and oxides thereof. For example, a polishing object having a surface made of a compound semiconductor material such as silicon carbide, boron carbide, tungsten carbide, silicon nitride, titanium nitride, gallium nitride, etc. can be processed by polishing (lapping) performed by supplying diamond abrasive grains between the polishing platen in contact with the surface of the polishing object and the polishing object. However, lapping using diamond abrasive grains is prone to defects and distortions due to the occurrence and remaining of scratches and dents. Therefore, polishing (polishing) performed by using a polishing pad and supplying a polishing liquid between the polishing pad and the polishing object after or instead of lapping using diamond abrasive grains has been considered. Patent documents 1 to 4 are cited as documents disclosing this type of conventional technology. [Prior art documents] [Patent documents]

[0003] [Patent Document 1] Japanese Patent Application Publication No. 2000-049124 [Patent Document 2] Japanese Patent Application Publication No. 2012-135863 [Patent Document 3] International Publication No. 2018 / 116521 [Patent Document 4] International Publication No. 2016 / 158328 Summary of the Invention [Problem to be solved by the invention]

[0004] In general, from the viewpoint of manufacturing efficiency and cost, it is desired that the polishing speed when polishing an object by supplying a polishing liquid is sufficiently high for practical use. For example, in polishing an object made of a high-hardness material such as silicon carbide, it is desired to further improve the polishing speed in order to improve the yield of the polished object.

[0005] When attempting to improve the polishing speed for this type of object to be polished by setting the polishing conditions, methods can be considered, such as increasing the load applied to the object to be polished during polishing to increase the processing pressure or increasing the rotation speed of the platen of the polishing device. However, in the above methods, there is a concern that problems such as damage to the object to be polished may occur due to an increase in frictional force. If a polishing liquid capable of effectively reducing the friction generated during polishing is provided, problems will be less likely to occur even when the polishing conditions are made more severe, such as high processing pressure and high-speed rotation of the platen, and this is beneficial for further improving the polishing speed.

[0006] The present invention has been made in view of the above circumstances, and an object of the present invention is to provide a polishing composition which can reduce friction against an object to be polished while maintaining a good polishing rate. [Means for solving the problem]

[0007] According to the present invention, there is provided a polishing composition comprising water, an abrasive grain, and a composite metal oxide as an oxidizing agent. The polishing composition further comprises an anionic polymer.

[0008] A combination of abrasive grains (e.g., alumina abrasive grains, silica abrasive grains, etc.) and a composite metal oxide can provide a polishing composition with excellent polishing power. Therefore, a composition containing water, abrasive grains, and a composite metal oxide is likely to improve the polishing rate. In addition, the anionic polymer can reduce friction while maintaining the polishing rate by acting on the surface to be polished and / or the surface of the abrasive grains of the object to be polished. Therefore, a polishing composition containing an anionic polymer in addition to water, abrasive grains, and a composite metal oxide can reduce friction against the object to be polished while exhibiting a good polishing rate.

[0009] According to a preferred embodiment of the present invention, there is provided a polishing composition comprising water, alumina abrasive grains, and a composite metal oxide as an oxidizing agent. The polishing composition further comprises an anionic polymer.

[0010] The combination of alumina abrasive grains and composite metal oxides can provide a polishing composition with excellent polishing power. Therefore, a composition containing water, alumina abrasive grains, and composite metal oxides can easily improve the polishing rate. In addition, the anionic polymer can reduce friction while maintaining the polishing rate by acting on the surface of the object to be polished and / or the surface of the alumina abrasive grains. Therefore, a polishing composition containing an anionic polymer in addition to water, alumina abrasive grains, and composite metal oxides can reduce friction against the object to be polished while showing a good polishing rate.

[0011] In a preferred embodiment of the technology disclosed herein, the anionic polymer is a homopolymer or copolymer that contains at least one of the following structural units in one molecule: structural unit derived from sulfonic acid, structural unit derived from (meth)acrylic acid, or structural unit derived from acrylamide.By using such anionic polymer, it is easy to realize a polishing composition that can show good polishing speed and reduce friction against the object to be polished (typically, the material to be polished).

[0012] In a preferred embodiment of the technology disclosed herein, the anionic polymer is a homopolymer or copolymer that contains at least one structural unit derived from styrenesulfonic acid, isoprene sulfonic acid, vinylsulfonic acid, allylsulfonic acid, isoamylenesulfonic acid, 2-(meth)acrylamide-2-methylpropanesulfonic acid or methallylsulfonic acid in one molecule.By using such anionic polymer, it is easy to realize a polishing composition that can show good polishing speed and reduce friction against the object to be polished.

[0013] In a preferred embodiment of the technology disclosed herein, the anionic polymer is a homopolymer or copolymer that contains at least one structural unit derived from acrylic acid or methacrylic acid in one molecule.By using such anionic polymer, it is easy to realize a polishing composition that can reduce friction against the object to be polished while showing a good polishing rate.

[0014] In a preferred embodiment of the technology disclosed herein, the anionic polymer is a copolymer that comprises a structural unit derived from sulfonic acid, a structural unit derived from (meth)acrylic acid and a structural unit derived from acrylamide.By using this anionic polymer, it is easy to realize a polishing composition that can show good polishing speed and reduce friction against polishing object.

[0015] The polishing composition according to a preferred embodiment of the present invention contains a permanganate as the composite metal oxide. With this configuration, the removal rate is likely to be improved.

[0016] A preferred embodiment of the polishing composition disclosed herein has a pH of 2.5 or more and 9.0 or less. In a polishing composition having a pH in the above range, the friction reducing effect of the anionic polymer tends to be favorably exhibited.

[0017] In a preferred embodiment of the technology disclosed herein, the polishing composition is used to polish a material having a Vickers hardness of 1500Hv or more. The effect of the present invention can be more preferably achieved in a polishing composition in which the material to be polished is a high-hardness material. In a preferred embodiment, the material having a Vickers hardness of 1500Hv or more is a non-oxide (i.e., a compound that is not an oxide). In polishing a non-oxide material to be polished, the polishing promotion effect of the oxidizing agent contained in the polishing composition disclosed herein is more likely to be preferably achieved.

[0018] This specification further provides a method for polishing an object to be polished. The method for polishing an object to be polished includes a step of polishing the object to be polished with any one of the polishing compositions disclosed herein. According to this method for polishing, even when an object to be polished is made of a high hardness material, the occurrence of defects such as damage to the object to be polished can be suppressed, and a high polishing rate can be achieved. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0019] Preferred embodiments of the present invention will be described below. Note that matters other than those specifically mentioned in this specification that are necessary for carrying out the present invention can be understood as design matters for a person skilled in the art based on the prior art in the relevant field. The present invention can be carried out based on the contents disclosed in this specification and the technical common sense in the relevant field.

[0020] <Polishing composition> (Abrasive grain) The material and properties of the abrasive grains are not particularly limited. For example, the abrasive grains may be any of inorganic particles, organic particles, and organic-inorganic composite particles. For example, the abrasive grains may be substantially composed of oxide particles such as silica particles, alumina particles, cerium oxide particles, chromium oxide particles, titanium dioxide particles, zirconium oxide particles, magnesium oxide particles, manganese dioxide particles, zinc oxide particles, and iron oxide particles; nitride particles such as silicon nitride particles and boron nitride particles; carbide particles such as silicon carbide particles and boron carbide particles; diamond particles; carbonates such as calcium carbonate and barium carbonate; and the like. The abrasive grains may be used alone or in combination of two or more kinds. Among them, oxide particles such as silica particles, alumina particles, cerium oxide particles, chromium oxide particles, zirconium oxide particles, manganese dioxide particles, and iron oxide particles are preferable because they can form a good surface. Among them, silica particles, alumina particles, zirconium oxide particles, chromium oxide particles, and iron oxide particles are more preferable, and silica particles and alumina particles are particularly preferable. In an embodiment in which silica particles or alumina particles are used as abrasive grains, the effect of reducing friction with respect to the object to be polished can be suitably exerted by applying the technology disclosed herein.

[0021] The abrasive grains function to mechanically polish the object to be polished. In a preferred embodiment of the technology disclosed herein, the polishing composition contains alumina grains (alumina abrasive grains) as abrasive grains. The alumina grains can be appropriately selected from various known alumina grains. Examples of such known alumina grains include α-alumina and intermediate alumina. Here, intermediate alumina is a general term for alumina grains other than α-alumina, and specific examples include γ-alumina, δ-alumina, θ-alumina, η-alumina, κ-alumina, and χ-alumina. In addition, alumina called fumed alumina (typically alumina fine particles produced when alumina salt is fired at high temperature) based on classification by manufacturing method may be used. Furthermore, alumina called colloidal alumina or alumina sol (for example, alumina hydrate such as boehmite) is also included in the above-mentioned known examples of alumina grains. From the viewpoint of processability, it is preferable to contain α-alumina. The alumina abrasive grains in the technology disclosed herein may contain one type of such alumina particles alone or two or more types in combination.

[0022] When using alumina particles as abrasive grains, it is generally advantageous to have a higher ratio of alumina particles to the entire abrasive grains used. For example, the ratio of alumina particles to the entire abrasive grains is preferably 70% by weight or more, more preferably 90% by weight or more, even more preferably 95% by weight or more, and may be substantially 100% by weight.

[0023] The particle size of the alumina abrasive grains is not particularly limited and may be selected so as to achieve a desired polishing effect. From the viewpoint of polishing efficiency, etc., the BET diameter of the alumina abrasive grains is preferably 0.05 μm or more, more preferably 0.1 μm or more, even more preferably 0.2 μm or more, and particularly preferably 0.3 μm or more. The upper limit of the BET diameter of the alumina abrasive grains is not particularly limited, but it is appropriate to set it to about 10 μm or less. From the viewpoint of improving surface quality, the BET diameter of the alumina abrasive grains is preferably 5 μm or less, more preferably 3 μm or less, and even more preferably 1 μm or less, for example, 0.8 μm or less. The range of the BET diameter of the alumina abrasive grains may be 0.2 μm or more and 1.0 μm or less, or may be 0.3 μm or more and 0.8 μm or less. In the technology disclosed herein, the BET diameter of the abrasive grains is, unless otherwise specified, calculated from the specific surface area (BET value) measured by the BET method, as BET diameter (nm) = 6000 / (true density (g / cm 3 ) × BET value (m 2 / g)) The BET diameter of the abrasive grains can typically be the average primary particle diameter of the abrasive grains. The BET diameter is measured by the method described in the Examples below.

[0024] When alumina particles are used as abrasive grains, the content of alumina abrasive grains in the polishing composition (when multiple types of alumina particles are included, the total content of them) is usually 1 wt% or more from the viewpoint of polishing efficiency. From the viewpoint of improving the polishing rate, the content of alumina abrasive grains in the polishing composition is preferably 3 wt% or more, more preferably 4 wt% or more, and may be 5 wt% or more. In addition, from the viewpoint of dispersibility, polishing stability, etc., the content of alumina abrasive grains in the polishing composition is usually 50 wt% or less, preferably 20 wt% or less, more preferably 15 wt% or less, may be 10 wt% or less, or may be 8 wt% or less.

[0025] When alumina particles are used as abrasive grains, the polishing composition disclosed herein may further contain abrasive grains made of materials other than the above-mentioned alumina (hereinafter also referred to as non-alumina abrasive grains) within the scope that does not impair the effects of the present invention. Examples of such non-alumina abrasive grains include abrasive grains substantially composed of any of oxide particles such as silica particles, cerium oxide particles, chromium oxide particles, titanium dioxide particles, zirconium oxide particles, magnesium oxide particles, manganese oxide particles, zinc oxide particles, and iron oxide particles; nitride particles such as silicon nitride particles and boron nitride particles; carbide particles such as silicon carbide particles and boron carbide particles; diamond particles; and carbonates such as calcium carbonate and barium carbonate.

[0026] The content of the non-alumina abrasive grains is suitably, for example, 30% by weight or less, preferably 20% by weight or less, and more preferably 10% by weight or less, of the total weight of the abrasive grains contained in the polishing composition.

[0027] In another preferred embodiment of the technology disclosed herein, the polishing composition contains silica particles (silica abrasive grains) as abrasive grains. The silica abrasive grains can be appropriately selected from various known silica particles. Examples of such known silica particles include colloidal silica, dry process silica, etc. Among them, the use of colloidal silica is preferred. The silica abrasive grains containing colloidal silica can suitably achieve good surface accuracy.

[0028] The shape (outer shape) of the silica abrasive grains may be spherical or non-spherical. For example, specific examples of non-spherical silica abrasive grains include a peanut shape (i.e., the shape of a peanut shell), a cocoon shape, a confetti shape, and a rugby ball shape. In the technology disclosed herein, the silica abrasive grains may be in the form of primary particles, or in the form of secondary particles in which a plurality of primary particles are associated. In addition, silica abrasive grains in the form of primary particles and silica abrasive grains in the form of secondary particles may be mixed. In a preferred embodiment, at least a portion of the silica abrasive grains are contained in the polishing composition in the form of secondary particles.

[0029] As the silica abrasive grains, those having a BET diameter of more than 5 nm can be preferably adopted. From the viewpoint of polishing efficiency, the BET diameter of the silica abrasive grains is preferably 15 nm or more, more preferably 20 nm or more, even more preferably 25 nm or more, and particularly preferably 30 nm or more. The upper limit of the BET diameter of the silica abrasive grains is not particularly limited, but it is appropriate to set it to about 120 nm or less, preferably 100 nm or less, more preferably 85 nm or less. For example, from the viewpoint of achieving both polishing efficiency and surface quality at a higher level, silica abrasive grains having a BET diameter of 12 nm or more and 80 nm or less are preferred, and silica abrasive grains having a BET diameter of 15 nm or more and 75 nm or less are preferred. The measurement of the BET diameter is performed by the method described in the examples below.

[0030] The average secondary particle diameter (hereinafter sometimes simply referred to as "D2") of the silica abrasive grains is not particularly limited, but from the viewpoint of polishing efficiency, etc., it is preferably 20 nm or more, more preferably 50 nm or more, and even more preferably 70 nm or more. Furthermore, from the viewpoint of obtaining a higher quality surface, the average secondary particle diameter D2 of the silica abrasive grains is appropriately 500 nm or less, preferably 300 nm or less, more preferably 200 nm or less, even more preferably 130 nm or less, and particularly preferably 110 nm or less (for example, 100 nm or less).

[0031] In the technology disclosed herein, the average secondary particle diameter of the abrasive grains can be measured as the volume-average particle diameter (arithmetic mean diameter based on volume; Mv) by dynamic light scattering using, for example, a model "UPA-UT151" manufactured by Nikkiso Co., Ltd.

[0032] When silica particles are used as abrasive grains, the content of silica abrasive grains in the polishing composition (when multiple types of silica particles are included, the total content of them) is usually 5% by weight or more from the viewpoint of polishing efficiency. From the viewpoint of improving the polishing rate, the content of silica abrasive grains in the polishing composition is preferably 10% by weight or more, more preferably 15% by weight or more, even more preferably 20% by weight or more, and may be 25% by weight or more. In addition, from the viewpoint of dispersibility, polishing stability, etc., the content of silica abrasive grains in the polishing composition is usually 60% by weight or less, preferably 50% by weight or less, more preferably 40% by weight or less, even more preferably 35% by weight or less, may be 32% by weight or less, or may be 30% by weight or less.

[0033] In addition, the polishing composition disclosed herein may be one that does not substantially contain diamond particles as abrasive grains. Diamond particles can be a limiting factor in improving smoothness due to their high hardness. In addition, diamond particles are generally expensive, so they are not considered to be advantageous materials in terms of cost performance, and from a practical standpoint, the degree of dependency on high-priced materials such as diamond particles may be low. Here, the abrasive grains that do not substantially contain diamond particles means that the proportion of diamond particles in the entire abrasive grains is 1% by weight or less, more preferably 0.5% by weight or less, typically 0.1% by weight or less, and includes the case where the proportion of diamond particles is 0% by weight. In such an embodiment, the application effect of the present invention can be preferably exhibited.

[0034] <Anionic polymer> The polishing composition disclosed herein contains an anionic polymer. The anionic polymer acts on the surface of the object to be polished and / or the surface of the abrasive grains, and can function as a friction reducer that reduces friction caused by direct contact between the abrasive grains and the object to be polished while maintaining a good polishing rate.

[0035] Here, the anionic polymer refers to a polymer having a repeating structural unit having an anionic group. The anionic group refers to a functional group that exhibits anionicity in at least a part of the pH range. The anionic polymer may be a homopolymer in which the repeating structural units constituting the anionic polymer are the same, or may be a copolymer in which the repeating structural units constituting the anionic polymer are different from each other. The anionic polymer disclosed herein is preferably a water-soluble polymer.

[0036] The above-mentioned anionic polymer can be, for example, a carboxylic acid polymer such as polyacrylic acid, a sulfonic acid polymer such as polystyrene sulfonic acid, etc. Such anionic polymer can exhibit a suitable friction reducing effect while maintaining a good polishing rate. Such anionic polymer can be used alone or in combination of two or more.

[0037] A preferred embodiment of the anionic polymer is a homopolymer or copolymer containing at least one of a sulfonic acid-derived structural unit, a (meth)acrylic acid-derived structural unit, or an acrylamide-derived structural unit in one molecule. Such an anionic polymer can exhibit a suitable friction reducing effect while maintaining a good polishing rate. Here, the term "(meth)acrylic acid" in this specification is a concept that includes one or both of acrylic acid and methacrylic acid. Such anionic polymers can be used alone or in combination of two or more.

[0038] In a preferred embodiment, a sulfonic acid polymer is used as the anionic polymer. Here, the sulfonic acid polymer refers to a polymer containing a structural unit X derived from a monomer having at least one sulfonic acid group in one molecule as a monomer unit constituting the sulfonic acid polymer. Examples of monomers having a sulfonic acid group include styrene sulfonic acid, isoprene sulfonic acid, vinyl sulfonic acid, allyl sulfonic acid, isoamylene sulfonic acid, 2-(meth)acrylamide-2-methylpropane sulfonic acid, and methallyl sulfonic acid. The sulfonic acid polymer preferably contains one or more structural units X derived from the above-mentioned sulfonic acid group-containing monomer. In addition, the sulfonic acid polymer may contain a component unit derived from a monomer other than the sulfonic acid group-containing monomer.

[0039] A suitable example of the sulfonic acid polymer disclosed herein is a sulfonic acid polymer A substantially composed of only a structural unit X derived from a sulfonic acid group-containing monomer. In other words, the sulfonic acid polymer A preferably has a molar ratio of the structural unit X to the total molar number of structural units contained in the molecular structure of the polymer of 99 mol % or more (e.g., 99.9 mol % or more, typically 99.9 to 100 mol %). Examples of such a sulfonic acid polymer A include a homopolymer composed of only one type of sulfonic acid group-containing monomer disclosed herein and a copolymer composed of two or more types of sulfonic acid group-containing monomers. Examples of homopolymers include polystyrene sulfonic acid, polyisoprene sulfonic acid, polyvinyl sulfonic acid, polyallyl sulfonic acid, and polyisoamylene sulfonic acid.

[0040] The weight average molecular weight (Mw) of the sulfonic acid polymer may be, for example, 500 or more, 1000 or more, or 2000 or more. From the viewpoint of improving the friction reducing effect, in some embodiments, the Mw of the sulfonic acid polymer is preferably 3000 or more, more preferably 5000 or more, 7000 or more, 9000 or more, 11000 or more, 20000 or more, or 30000 or more. The upper limit of the Mw of the sulfonic acid polymer is not particularly limited, but may be, for example, 150×10 4 may be less than or equal to 100×10 4 Less than 50×10 is fine. 4 Less than 30×10 is fine. 4 Less than 20×10 is fine. 4 Less than 10 x 10 is fine. 4 Less than 7×10 is fine. 4 The Mw of the sulfonic acid copolymer may be the weight average molecular weight (water-based, polyethylene glycol equivalent) determined by gel permeation chromatography (GPC).

[0041] Another preferred example of the sulfonic acid polymer disclosed herein is a (meth)acrylic acid / sulfonic acid copolymer containing a structural unit derived from (meth)acrylic acid and a structural unit X derived from a sulfonic acid group-containing monomer. Such a (meth)acrylic acid / sulfonic acid copolymer may contain one or more types of structural units X derived from the above-mentioned sulfonic acid group-containing monomer. In addition, it may contain a component derived from a monomer other than the sulfonic acid group-containing monomer and the (meth)acrylic acid monomer. Examples of the (meth)acrylic acid / sulfonic acid copolymer include a (meth)acrylic acid / isoprene sulfonic acid copolymer, a (meth)acrylic acid / 2-acrylamido-2-methylpropane sulfonic acid copolymer, and a (meth)acrylic acid / isoprene sulfonic acid / 2-acrylamido-2-methylpropane sulfonic acid copolymer. For example, the (meth)acrylic acid / sulfonic acid copolymer may contain a component derived from an acrylamide monomer in addition to the sulfonic acid group-containing monomer and the (meth)acrylic acid monomer. An example of the (meth)acrylic acid / sulfonic acid copolymer is a (meth)acrylic acid / 2-acrylamide-2-methylpropanesulfonic acid copolymer.

[0042] The molecular weight of the (meth)acrylic acid / sulfonic acid copolymer may be, for example, 500 or more, 1000 or more, or 2000 or more. From the viewpoint of improving the friction reducing effect, in some embodiments, the Mw of the (meth)acrylic acid / sulfonic acid copolymer is preferably 3000 or more, more preferably 5000 or more, may be 7000 or more, or may be 9000 or more. The upper limit of the Mw of the (meth)acrylic acid / sulfonic acid copolymer is not particularly limited, but may be, for example, 150×10 4 may be less than or equal to 100×10 4 Less than 50×10 is fine. 4 Less than 30×10 is fine. 4 Less than 20×10 is fine. 4 Less than 10 x 10 is fine. 4 Less than 7×10 is fine. 4 Less than 5×10 is fine. 4 Less than 3×10 is fine. 4 Less than 1.5×10 is also acceptable.4 As the Mw of the (meth)acrylic acid / sulfonic acid copolymer, the weight average molecular weight (water-based, polyethylene glycol equivalent) determined by GPC can be used.

[0043] The (meth)acrylic acid / sulfonic acid copolymer may be a random copolymer, a block copolymer, or a graft copolymer. The ratio (molar ratio) of the number of moles of the structural unit X derived from a sulfonic acid group-containing monomer to the number of moles of all repeating units constituting the (meth)acrylic acid / sulfonic acid copolymer is not particularly limited. The ratio may be, for example, 5 mol% or more, or 10 mol% or more. From the viewpoint of improving the friction reduction effect, in one embodiment, the ratio may be 20 mol% or more (for example, 25 mol% or more). In another embodiment, the ratio may be, for example, 95 mol% or less, 90 mol% or less, 80 mol% or less, or even 70 mol% or less (for example, 40 mol% or less).

[0044] In a preferred embodiment, a (meth)acrylic acid-based polymer containing a structural unit derived from (meth)acrylic acid is used as the anionic polymer. Typical examples of the (meth)acrylic acid-based polymer include polyacrylic acid and polymethacrylic acid. Among these, polyacrylic acid is preferred.

[0045] The Mw of the (meth)acrylic acid-based polymer may be, for example, 500 or more, 700 or more, 1000 or more, or 1500 or more. The upper limit of the Mw of the (meth)acrylic acid-based polymer is not particularly limited, but may be, for example, 15×10 4 may be less than or equal to 10 x 10 4 Less than 5×10 is fine. 4 Less than 1×10 is fine. 4 It may be 7000 or less, 5000 or less, or 4000 or less. As the Mw of the (meth)acrylic acid polymer, the weight average molecular weight (water-based, polyethylene glycol equivalent) determined by GPC can be used.

[0046] The anionic polymer may be used in the form of a neutralized salt, such as an alkali metal salt (e.g., Na or K), an ammonium salt, or an alkyl ammonium salt.

[0047] The Mw of the anionic polymer may be, for example, 500 or more, 700 or more, 1000 or more, or 1500 or more. The upper limit of the Mw of the anionic polymer is not particularly limited, but may be, for example, 150×10 4 may be less than or equal to 100×10 4 Less than 50×10 is fine. 4 Less than 30×10 is fine. 4 Less than 20×10 is fine. 4 Less than 10 x 10 is fine. 4 Less than 7×10 is fine. 4 As the Mw of the anionic polymer, a weight average molecular weight (water-based, polyethylene glycol equivalent) determined by GPC can be used.

[0048] The content of the anionic polymer in the polishing composition (in an embodiment containing a plurality of anionic polymers, the total content thereof) is not particularly limited. The content of the anionic polymer is, for example, suitably 0.001 g / L or more (or more than 0.001 g / L). From the viewpoint of effectively exerting the friction reducing effect, the content is preferably 0.005 g / L or more (or more than 0.005 g / L), more preferably 0.01 g / L or more, and even more preferably 0.05 g / L or more. In addition, from the viewpoint of maintaining a good polishing rate, the content is suitably 5.0 g / L or less, preferably 2.0 g / L or less, more preferably 1.0 g / L or less, and may be, for example, 0.8 g / L or less, 0.6 g / L or less, or 0.3 g / L or less.

[0049] For example, when a (meth)acrylic acid-based polymer is used as the anionic polymer, the content of the (meth)acrylic acid-based polymer in the polishing composition is not particularly limited. The content of the (meth)acrylic acid-based polymer is, for example, suitably 0.001 g / L or more (or more than 0.001 g / L). From the viewpoint of effectively exerting the friction reduction effect, the content is preferably 0.005 g / L or more (or more than 0.005 g / L), more preferably 0.01 g / L or more, and even more preferably 0.05 g / L or more. In addition, from the viewpoint of maintaining a good polishing rate, the content is suitably 5.0 g / L or less, preferably 2.0 g / L or less, more preferably 1.0 g / L or less, and may be, for example, 0.8 g / L or less, 0.6 g / L or less, 0.5 g / L or less, or 0.25 g / L or less.

[0050] <Non-anionic polymer> The polishing composition disclosed herein may or may not further contain a polymer (non-anionic polymer) other than the anionic polymer. As the non-anionic polymer, any of a nonionic polymer, a cationic polymer, and an amphoteric polymer can be used. The non-anionic polymer is preferably a water-soluble polymer.

[0051] Examples of non-anionic polymers that can be used in the polishing composition disclosed herein include polymers containing nitrogen atoms.Non-limiting examples of polymers containing nitrogen atoms include polymers containing N-vinyl type monomer units; polymers containing N-(meth)acryloyl type monomer units; and the like.Examples of polymers containing N-vinyl type monomer units include polymers containing repeating units derived from monomers having nitrogen-containing heterocycles (e.g., lactam rings).Examples of such polymers include homopolymers and copolymers of N-vinyl lactam type monomers (e.g., copolymers in which the copolymerization ratio of N-vinyl lactam type monomers is more than 50% by weight).

[0052] Specific examples of N-vinyl lactam type monomers (i.e., compounds having a lactam structure and an N-vinyl group in one molecule) include N-vinyl pyrrolidone (VP), N-vinyl piperidone, N-vinyl morpholinone, N-vinyl caprolactam (VC), N-vinyl-1,3-oxazin-2-one, and N-vinyl-3,5-morpholinedione. Specific examples of polymers containing N-vinyl lactam type monomer units include polyvinyl pyrrolidone, polyvinyl caprolactam, random copolymers of VP and VC, random copolymers of one or both of VP and VC and other vinyl monomers (e.g., acrylic monomers, vinyl ester monomers, etc.), block copolymers and graft copolymers containing polymer chains containing one or both of VP and VC, etc. Specific examples of polymers containing one of VP and VC include polyvinyl pyrrolidone vinyl acetate copolymers, etc.

[0053] Examples of polymers containing N-(meth)acryloyl type monomer units include homopolymers and copolymers of N-(meth)acryloyl type monomers (e.g., copolymers in which the copolymerization ratio of N-(meth)acryloyl type monomers exceeds 50% by weight). Examples of N-(meth)acryloyl type monomers include cyclic amides having an N-(meth)acryloyl group.

[0054] Examples of cyclic amides having an N-(meth)acryloyl group include N-acryloylmorpholine, N-acryloylthiomorpholine, N-acryloylpiperidine, N-acryloylpyrrolidine, N-methacryloylmorpholine, N-methacryloylpiperidine, and N-methacryloylpyrrolidine. Examples of polymers containing cyclic amides having an N-(meth)acryloyl group as monomer units include acryloylmorpholine-based polymers (PACMO). Typical examples of acryloylmorpholine-based polymers include homopolymers of N-acryloylmorpholine (ACMO) and copolymers of ACMO (e.g., copolymers with a copolymerization ratio of ACMO exceeding 50% by weight). In the acryloylmorpholine-based polymer, the ratio (molar ratio) of the number of moles of ACMO units to the number of moles of all repeating units is usually 50 mol% or more, and suitably 80 mol% or more (e.g., 90 mol% or more, or 95 mol% or more). All repeating units of the non-anionic polymer may be substantially composed of ACMO units.

[0055] Specific examples of non-anionic polymers include polyvinyl acetate, etc. Specific examples of non-anionic polymers include polyaluminum chloride, polyferric sulfate, etc.

[0056] The non-anionic polymers can be used alone or in combination of two or more.

[0057] The content of the non-anionic polymer (in an embodiment containing a plurality of non-anionic polymers, the total content thereof) is not particularly limited. From the viewpoint of maintaining a good polishing rate, the content of the anionic polymer W X Non-anionic polymer content W [wt%] Y [weight%] ratio (W Y / W X ) is preferably less than 1, more preferably 0.5 or less, further preferably 0.2 or less, and particularly preferably 0.1 or less.

[0058] From the viewpoint of maintaining a better polishing rate, the polishing composition can be preferably implemented in the form of not substantially containing non-anionic polymer.Here, not substantially containing non-anionic polymer means that at least intentionally not containing non-anionic polymer, typically means that the content of non-anionic polymer in the polishing composition is 0.001wt% or less, preferably 0.0001wt% or less, and includes that the content of non-anionic polymer is 0wt%.

[0059] (Oxidizing agent) The polishing composition disclosed herein contains an oxidizing agent. The oxidizing agent can exhibit the effect of improving the polishing rate in polishing an object to be polished (e.g., silicon carbide). The polishing composition disclosed herein contains a complex metal oxide as an oxidizing agent. Examples of the complex metal oxide include metal nitrates, ferric acids, permanganic acids, chromic acids, vanadic acids, ruthenic acids, molybdic acids, rhenic acids, and tungstic acids. Among them, ferric acids, permanganic acids, and chromic acids are more preferable, and permanganic acids (e.g., permanganate) are even more preferable.

[0060] Specific examples of the composite metal oxide include metal nitrates such as iron nitrate and silver nitrate, ferric acids such as potassium ferrate, permanganic acids such as sodium permanganate and potassium permanganate, chromates such as potassium chromate and potassium dichromate, vanadic acids such as sodium vanadate and potassium vanadate, ruthenic acids such as perruthenic acid salts, molybdic acids such as ammonium molybdate and disodium molybdate, rhenic acids such as perrhenic acid salts, and tungstic acids such as disodium tungstate. The composite metal oxides can be used alone or in combination of two or more.

[0061] In some particularly preferred embodiments, the composite metal oxide is a composite metal oxide having a monovalent or divalent metal element (excluding transition metal elements) and a fourth period transition metal element of the periodic table. Suitable examples of the monovalent or divalent metal element include Na, K, Mg, and Ca. Of these, Na and K are more preferred. Suitable examples of the fourth period transition metal element of the periodic table include Fe, Mn, Cr, V, and Ti. Of these, Fe, Mn, and Cr are more preferred, and Mn is even more preferred. The composite metal oxide can effectively reduce the hardness and weaken the surface of a high-hardness material such as silicon carbide. This can more preferably exhibit the effect of improving the polishing rate.

[0062] When the composite metal oxide is a salt (for example, permanganate), the composite metal oxide may be present in the polishing composition in the form of ions.

[0063] The polishing composition disclosed herein may further contain an oxidizing agent other than the composite metal oxide. Examples of the oxidizing agent other than the composite metal oxide include peroxides such as hydrogen peroxide. The technology disclosed herein can be preferably implemented in an embodiment in which a composite metal oxide (e.g., vanadates) and an oxidizing agent other than the composite metal oxide (e.g., hydrogen peroxide) are used in combination as an oxidizing agent.

[0064] In an embodiment in which hydrogen peroxide and vanadic acids (e.g., sodium metavanadate) are used in combination as the oxidizing agent, the ratio (C2 / C1) of the hydrogen peroxide content C2 to the vanadic acids content C1 is not particularly limited and is suitably 0.5 to 5, preferably 1 to 4, and more preferably 1.5 to 3, on a weight basis. By using the above compounds in combination so as to achieve a specific content ratio, it is possible to achieve a higher level of compatibility between the polishing rate and the surface quality.

[0065] The polishing composition disclosed herein may not contain an oxidizing agent other than the composite metal oxide. The technique disclosed herein can also be preferably implemented in an embodiment that does not substantially contain an oxidizing agent (e.g., hydrogen peroxide) other than the composite metal oxide.

[0066] The content of the oxidizing agent (e.g., permanganate) in the polishing composition is usually appropriate to be 0.005 mol / L or more. From the viewpoint of polishing efficiency, the content of the oxidizing agent (e.g., permanganate) is preferably 0.008 mol / L or more, more preferably 0.01 mol / L or more, may be 0.03 mol / L or more, may be 0.05 mol / L or more, may be 0.06 mol / L or more, or may be 0.07 mol / L or more. From the viewpoint of surface quality after polishing, the content of the oxidizing agent (e.g., permanganate) in the polishing composition is usually appropriate to be 0.5 mol / L or less, preferably 0.3 mol / L or less, more preferably 0.2 mol / L or less, may be 0.1 mol / L or less, or may be 0.09 mol / L or less.

[0067] In another preferred embodiment, the content of the oxidizing agent (e.g., vanadic acids) in the polishing composition is usually 0.005 mol / L or more. From the viewpoint of polishing efficiency, the content of the oxidizing agent (e.g., vanadic acids) is preferably 0.01 mol / L or more, more preferably 0.05 mol / L or more, may be 0.08 mol / L or more, may be 0.1 mol / L or more, may be 0.15 mol / L or more, or may be 0.18 mol / L or more. From the viewpoint of surface quality after polishing, the content of the oxidizing agent (e.g., vanadic acids) in the polishing composition is usually 1.0 mol / L or less, preferably 0.8 mol / L or less, more preferably 0.5 mol / L or less, may be 0.3 mol / L or less, or may be 0.2 mol / L or less.

[0068] In another preferred embodiment, the content of the oxidizing agent (e.g., hydrogen peroxide) other than the composite metal oxide in the polishing composition is usually 0.05 mol / L or more. From the viewpoint of polishing efficiency, the content of the oxidizing agent (e.g., hydrogen peroxide) other than the composite metal oxide is preferably 0.1 mol / L or more, more preferably 0.2 mol / L or more, may be 0.25 mol / L or more, may be 0.3 mol / L or more, may be 0.35 mol / L or more, or may be 0.4 mol / L or more. From the viewpoint of surface quality after polishing, the content of the oxidizing agent (e.g., hydrogen peroxide) other than the composite metal oxide in the polishing composition is usually 5.0 mol / L or less, preferably 2 mol / L or less, more preferably 1 mol / L or less, may be 0.7 mol / L or less, or may be 0.5 mol / L or less.

[0069] (water) The polishing composition disclosed herein contains water. As the water, ion-exchanged water (deionized water), pure water, ultrapure water, distilled water, etc. can be preferably used. The polishing composition disclosed herein may further contain an organic solvent (lower alcohol, lower ketone, etc.) that can be uniformly mixed with water, if necessary. Usually, it is appropriate that 90% by volume or more of the solvent contained in the polishing composition is water, preferably 95% by volume or more is water, and more preferably 99 to 100% by volume is water.

[0070] (acid) The polishing composition may contain an acid as necessary for the purpose of pH adjustment, polishing acceleration, etc. As the acid, both inorganic and organic acids can be used. Examples of inorganic acids include sulfuric acid, nitric acid, hydrochloric acid, carbonic acid, etc. Examples of organic acids include aliphatic carboxylic acids such as formic acid, acetic acid, and propionic acid, aromatic carboxylic acids such as benzoic acid and phthalic acid, citric acid, oxalic acid, tartaric acid, malic acid, maleic acid, fumaric acid, succinic acid, organic sulfonic acid, and organic phosphonic acid. These may be used alone or in combination of two or more. When an acid is used, the amount of the acid is not particularly limited, and may be the amount according to the purpose of use (e.g., pH adjustment). Alternatively, in some embodiments of the polishing composition disclosed herein, the composition may be substantially free of acid.

[0071] (Basic compounds) The polishing composition may contain a basic compound as necessary for the purpose of pH adjustment, polishing acceleration, etc. Here, the basic compound refers to a compound that has the function of increasing the pH of the polishing composition by being added to the polishing composition. Examples of basic compounds include alkali metal hydroxides such as potassium hydroxide and sodium hydroxide; carbonates and bicarbonates such as ammonium hydrogen carbonate, ammonium carbonate, potassium hydrogen carbonate, potassium carbonate, sodium hydrogen carbonate, and sodium carbonate; ammonia; quaternary ammonium hydroxides such as quaternary ammonium hydroxides such as tetramethylammonium hydroxide, tetraethylammonium hydroxide, and tetrabutylammonium hydroxide; amines, phosphates, hydrogen phosphates; and organic acid salts. The basic compounds may be used alone or in combination of two or more. When a basic compound is used, the amount used is not particularly limited and may be an amount depending on the purpose of use (e.g., pH adjustment). Alternatively, in some embodiments of the polishing composition disclosed herein, the composition may be substantially free of a basic compound.

[0072] (Other Ingredients) The polishing composition disclosed herein may further contain, as necessary, known additives that can be used in polishing compositions (for example, polishing compositions used for polishing high-hardness materials such as silicon carbide), such as chelating agents, thickening agents, dispersants, surface protective agents, wetting agents, surfactants, rust inhibitors, preservatives, and antifungal agents, within the scope that does not impair the effects of the present invention. The content of the above additives may be appropriately set according to the purpose of their addition, and detailed explanations are omitted since they do not characterize the present invention.

[0073] (Oxidation-Reduction Potential) The oxidation-reduction potential (hereinafter, also referred to as ORP: Oxidation-Reduction Potential) of the polishing composition disclosed herein is not particularly limited. From the viewpoint of polishing efficiency, etc., the ORP of the polishing composition is appropriate to be 400mV or more, preferably 600mV or more, more preferably 650mV or more (for example, 750mV or more, or 800mV or more). The upper limit of the ORP of the polishing composition is not particularly limited, but from the viewpoint of easily obtaining a higher quality surface, etc., it is preferably 1500mV or less, more preferably 1300mV or less, and even more preferably 1200mV or less (for example, 1000mV or less, or 950mV or less).

[0074] By appropriately selecting the type of abrasive grains and oxidizing agent, or the ratio of the content of abrasive grains and oxidizing agent, the ORP of the polishing composition can be adjusted.In addition, the method of adjusting the ORP of the polishing composition can also be adopted by changing the pH of the composition.The above-mentioned methods of controlling ORP can be used alone or in combination.The ORP of the polishing composition is measured by the method described in the examples below.

[0075] (Zeta potential) According to the technology disclosed herein, the addition of an anionic polymer exerts a friction reducing effect. Such a friction reducing effect can be exerted more significantly when an anionic polymer is further added to a composition C0 containing abrasive grains exhibiting a predetermined zeta potential ζ0. The absolute value of the zeta potential ζ0 of the abrasive grains in the composition C0 before the addition of the anionic polymer (typically a composition having the same composition as the polishing composition except that it does not contain an anionic polymer) is preferably 110 mV or less, more preferably 90 mV or less, even more preferably 70 mV or less, particularly preferably 50 mV or less, and may be, for example, 40 mV or less, 30 mV or less, or 25 mV or less. In a configuration in which the absolute value of the zeta potential ζ0 of the abrasive grains in the composition C0 is equal to or less than the above-mentioned predetermined value, the friction reducing effect by using the anionic polymer disclosed herein is preferably exerted. The zeta potential ζ0 of the abrasive grains in the composition C0 is measured by the method described in the Examples below.

[0076] The reason why the friction reducing effect is improved when an anionic polymer is added to a composition C0 containing abrasive grains exhibiting a zeta potential ζ0 in a predetermined range is not particularly limited, but may be, for example, as follows. That is, in a composition C0 in which the absolute value of the zeta potential ζ0 of the abrasive grains is relatively large, the abrasive grains are considered to be well dispersed due to electrical repulsion between each other. On the other hand, in a composition C0 in which the absolute value of the zeta potential ζ0 of the abrasive grains is relatively small, the dispersibility of the abrasive grains tends to decrease. Here, it is considered that the anionic polymer acts on the abrasive grain surface, etc., thereby suppressing direct contact between the abrasive grains and the object to be polished. Such a friction reducing effect by adding an anionic polymer can be more effectively exhibited in a composition C0 in which the dispersibility of the abrasive grains tends to decrease. For this reason, when an anionic polymer is added to a composition C0 in which the absolute value of the zeta potential ζ0 of the abrasive grains is equal to or less than a predetermined value, the friction reducing effect is particularly likely to be improved.

[0077] The zeta potential ζ of the abrasive grains in the polishing composition disclosed herein A The zeta potential ζ of the abrasive grains in the polishing composition is not particularly limited. AThe absolute value of the zeta potential ζ is usually 5 mV or more, preferably 10 mV or more, more preferably 13 mV or more, for example 20 mV or more. A The larger the absolute value of zeta potential ζ, the stronger the electrical repulsion between the abrasive grains, and the more the dispersion stability of the abrasive grains in the polishing composition tends to improve. A The upper limit of the absolute value of the zeta potential ζ of the abrasive grains in the polishing composition is not particularly limited, but is usually 175 mV or less, preferably 100 mV or less, more preferably 80 mV or less, and further preferably 70 mV or less (for example, 60 mV or less, or 50 mV or less). A is measured by the method described in the Examples below.

[0078] (pH) The pH of the polishing composition is usually about 2 to 12. When the pH is in the above range, a practical polishing rate is easily achieved in polishing the object to be polished. In some embodiments, the pH may be 2.5 or more, 3.0 or more, 4.0 or more, 5.0 or more, or 5.5 or more. The upper limit of the pH is not particularly limited, but in some embodiments, the pH may be 12.0 or less, 10.0 or less, 9.0 or less (e.g., less than 9.0), 8.0 or less (e.g., less than 8.0), 7.0 or less, or 6.8 or less.

[0079] The pH of the polishing composition is determined by the zeta potential ζ of the particles in the polishing composition. A In the technology disclosed herein, the zeta potential ζ that can more effectively exert the friction reduction effect can be influenced. A From the viewpoint of adjusting to pH 3.0 or more, more preferably pH 4.0 or more, and even more preferably pH 5.0 or more (e.g., pH 5.5 or more). From the viewpoint of improving the friction reducing effect by stabilizing the ionized state of the anionic polymer in the polishing composition, the pH of the polishing composition is preferably pH 8.0 or less, more preferably pH 7.0 or less, and even more preferably pH 6.8 or less.

[0080] In a preferred embodiment of the polishing composition disclosed herein, the pH of the polishing composition is 4.0 or more and less than 8.0. Within this pH range, the friction reducing effect of anionic polymer tends to be favorably exhibited. From this viewpoint, the pH of the polishing composition is more preferably 5.0 or more and 7.0 or less, and even more preferably 5.5 or more and 6.8 or less.

[0081] (Electrical Conductivity) The electrical conductivity of the polishing composition disclosed herein is not particularly limited. The electrical conductivity of the polishing composition is usually 5 mS / cm or more, preferably 7 mS / cm or more, and more preferably 8 mS / cm or more (e.g., 8.5 mS / cm or more, or 8.6 mS / cm or more). The upper limit of the electrical conductivity of the polishing composition is not particularly limited, but is usually 40 mS / cm or less, preferably 30 mS / cm or less, more preferably 15 mS / cm or less, even more preferably 13 mS / cm or less, and particularly preferably 11 mS / cm or less (e.g., 10.5 mS / cm or less, or 8.8 mS / cm or less). In the polishing composition showing the electrical conductivity in the above-mentioned predetermined range, the friction reducing effect by using the anionic polymer disclosed herein is preferably exhibited.

[0082] In this specification, the electrical conductivity of the polishing composition refers to the electrical conductivity measured under the condition that the content of abrasive grains in the polishing composition is 6% by weight. The electrical conductivity of the polishing composition is measured by the method described in the Examples below.

[0083] The method for adjusting the electrical conductivity of the polishing composition is not particularly limited. For example, the electrical conductivity can be adjusted by blending an appropriate amount of electrolyte (salt, acid, alkali, etc.) into the polishing composition, diluting or concentrating the polishing composition, or subjecting a part or all of the components of the polishing composition to ion exchange treatment. The method for adjusting electrical conductivity may be used alone or in combination of two or more.

[0084] The method of preparing the polishing composition disclosed herein is not particularly limited.For example, it is advisable to use a well-known mixing device such as a blade type agitator, an ultrasonic disperser, a homomixer, etc. to mix each component contained in the polishing composition.The manner of mixing these components is not particularly limited, and for example, all components may be mixed at once, or may be mixed in a suitably set order.

[0085] (characteristic) The polishing composition according to a preferred embodiment disclosed herein satisfies the following characteristics with respect to the friction coefficient and polishing rate measured in a polishing test carried out under specified conditions. That is, in a polishing test carried out by using a polishing pad and supplying a polishing liquid between the polishing pad and an object to be polished, the friction coefficient F measured using the polishing composition as the polishing liquid is 0.01 to 0.01 mm. A and polishing rate R A The friction coefficient F0 and the removal rate R0 measured using a comparative composition having the same composition as the polishing composition except that the polishing liquid does not contain the anionic polymer are in the following relationship: F A / F0 ≤ 0.9; and R A / R0>0.8;

[0086] According to the polishing composition that satisfies such characteristics, the friction with the object to be polished is reduced while maintaining a good polishing rate.Therefore, the polishing composition that satisfies such characteristics is likely to improve the degree of freedom of polishing conditions when polishing.Therefore, the polishing composition that satisfies such characteristics can further improve the polishing rate of the object to be polished when polishing.

[0087] Here, the polishing test is carried out by the method described in the Examples below. That is, the object to be polished in the polishing test is one described in the Examples below. Furthermore, polishing in the polishing test is carried out under the conditions described in the Examples below. Friction coefficient F A and F0 and the polishing rate R Aand R0 are measured by the methods described in the following examples. Typically, the pH of the polishing composition is equal to or close to the pH of the comparative composition. The difference between the pH of the polishing composition and the pH of the comparative composition is preferably 2.0 or less, more preferably 1.5 or less, and even more preferably 1.0 or less (e.g., 0.8 or less), and may be 0.5 or less, 0.3 or less, or 0.2 or less.

[0088] F is the ratio of the coefficient of friction between the polishing composition and the comparative composition in the above polishing test. A From the viewpoint of reducing friction, F is preferably 0.95 or less, more preferably 0.9 or less, and even more preferably 0.85 or less (for example, 0.81 or less). A The lower limit of / F0 is not particularly limited, but from the viewpoint of maintaining a good polishing rate, it may be 0.5 or more, 0.6 or more, or 0.7 or more.

[0089] R is the ratio of the polishing rate between the polishing composition and the comparative composition in the above polishing test. A From the viewpoint of improving the polishing rate, R is more preferably 0.9 or more, further preferably 0.95 or more, and particularly preferably 0.98 or more (for example, 1 or more). A Although there is no particular upper limit for / R0 (polishing speed ratio), from the viewpoint of reducing friction, R A / R0 is equal to or less than 1.5, and may be equal to or less than 1.3.

[0090] <Object to be polished> The object to be polished by the polishing composition disclosed herein is not particularly limited. For example, the polishing composition disclosed herein can be applied to polishing a substrate having a surface made of a compound semiconductor material, that is, a compound semiconductor substrate. The constituent material of the compound semiconductor substrate is not particularly limited, and can be, for example, II-VI group compound semiconductors such as cadmium telluride, zinc selenide, cadmium sulfide, mercury cadmium telluride, zinc cadmium telluride, etc.; III-V group compound semiconductors such as gallium nitride, gallium arsenide, gallium phosphide, indium phosphide, aluminum gallium arsenide, indium gallium arsenide, indium gallium nitride arsenide, aluminum gallium indium phosphide, etc.; IV-IV group compound semiconductors such as silicon carbide, germanium silicide, etc. The object to be polished may be made of a plurality of these materials. In a preferred embodiment, the polishing composition disclosed herein can be applied to polishing a substrate having a surface made of a chemical semiconductor material that is not an oxide (i.e., a non-oxide). In polishing a substrate having a surface composed of a non-oxide chemical semiconductor material, the polishing-accelerating effect of the oxidizing agent contained in the polishing composition disclosed herein is easily and suitably exhibited.

[0091] The polishing composition disclosed herein can be preferably used for polishing the surface of the object to be polished having a Vickers hardness of, for example, 500Hv or more. The Vickers hardness is preferably 700Hv or more, for example, 1000Hv or more, or 1500Hv or more. The Vickers hardness of the material to be polished may be 1800Hv or more, 2000Hv or more, or 2200Hv or more. Materials with high Vickers hardness tend to be brittle and weak against impact, and are easily damaged depending on the polishing conditions. For this reason, it is more meaningful to apply the polishing composition of the present invention to such a material to be polished. The upper limit of the Vickers hardness of the surface of the object to be polished is not particularly limited, and may be, for example, about 7000Hv or less, 5000Hv or less, or 3000Hv or less. In this specification, the Vickers hardness can be measured based on JIS R 1610:2003. The international standard corresponding to the above JIS standard is ISO 14705:2000.

[0092] Examples of materials having a Vickers hardness of 1500Hv or more include silicon carbide, silicon nitride, titanium nitride, gallium nitride, etc. The object to be polished in the technology disclosed herein may have a single crystal surface of the above material that is mechanically and chemically stable. In particular, the surface of the object to be polished is preferably composed of either silicon carbide or gallium nitride, and more preferably composed of silicon carbide. Silicon carbide is expected to be a compound semiconductor substrate material with low power loss and excellent heat resistance, etc., and the practical advantage of improving its surface properties is particularly great. The technology disclosed herein can be particularly preferably applied to polishing the single crystal surface of silicon carbide.

[0093] <Polishing method> The polishing composition disclosed herein can be used for polishing an object to be polished, for example, in an embodiment including the following steps. That is, prepare a polishing liquid (slurry) containing any of the polishing compositions disclosed herein. The preparation of the polishing liquid may include adjusting the concentration (e.g., dilution), adjusting pH, etc., of the polishing composition to prepare the polishing liquid. Alternatively, the polishing composition may be used as it is as the polishing liquid. In addition, in the case of a multi-agent type polishing composition, the preparation of the polishing liquid may include mixing the agents, diluting one or more agents before the mixing, diluting the mixture after the mixing, etc. Next, the polishing liquid is supplied to the object to be polished, and the object is polished by a normal method used by those skilled in the art. For example, the object to be polished is set in a general polishing device, and the polishing liquid is supplied to the surface of the object to be polished through the polishing pad of the polishing device. Typically, the polishing liquid is continuously supplied, and the polishing pad is pressed against the surface of the object to be polished, and the two are moved relatively (for example, rotated). Through this polishing process, the polishing of the object to be polished is completed.

[0094] According to this specification, a polishing method for polishing an object to be polished (typically, a material to be polished) and a method for manufacturing a polished product using the polishing method are provided. The polishing method is characterized by including a step of polishing an object to be polished using the polishing composition disclosed herein. A preferred embodiment of the polishing method includes a step of performing pre-polishing (pre-polishing step) and a step of performing finish polishing (finish polishing step). In a typical embodiment, the pre-polishing step is a polishing step arranged immediately before the finish polishing step. The pre-polishing step may be a polishing step of one stage, or a polishing step of two or more stages. The finish polishing step here refers to a polishing step that performs finish polishing on an object to be polished that has been subjected to pre-polishing, and is arranged at the end (i.e., the most downstream side) of the polishing steps that are performed using a polishing slurry containing abrasive grains. In such a polishing method including a pre-polishing step and a finish polishing step, the polishing composition disclosed herein may be used in the pre-polishing step, may be used in the finish polishing step, or may be used in both the pre-polishing step and the finish polishing step.

[0095] In a preferred embodiment, the polishing step using the above-mentioned polishing composition can be a preliminary polishing step.When the preliminary polishing step includes two or more stages of polishing steps, two or more of the polishing steps can be carried out using any of the polishing compositions disclosed herein.The polishing composition disclosed herein can be preferably applied to the preliminary polishing at the front stage (upstream side).For example, it can also be preferably used in the first preliminary polishing step after the lapping step described below, typically in the first polishing step.

[0096] In another preferred embodiment, the polishing process using the above-mentioned polishing composition is a finish polishing process.The polishing composition disclosed herein can reduce the number of dents and defects on the surface after polishing, and is therefore suitable as a polishing composition (finish polishing composition) used in the finish polishing process of the surface of the object to be polished.

[0097] Preliminary polishing and finish polishing can be applied to both polishing using a single-sided polishing machine and polishing using a double-sided polishing machine. In a single-sided polishing machine, the object to be polished is attached to a ceramic plate with wax or held using a holding tool called a carrier, and one side of the object to be polished is polished by pressing a polishing pad against one side of the object to be polished while supplying a polishing composition, and moving the two relatively. The above movement is, for example, a rotational movement. In a double-sided polishing machine, the object to be polished is held using a holding tool called a carrier, and while supplying a polishing composition from above, a polishing pad is pressed against the opposing side of the object to be polished, and the two are rotated in a relative direction to polish both sides of the object to be polished simultaneously.

[0098] The polishing pad used in each polishing step disclosed herein is not particularly limited. For example, any of nonwoven type, suede type, hard foam polyurethane type, abrasive type, abrasive type, and the like may be used. In some embodiments, a suede type polishing pad that does not contain abrasive particles may be preferably used.

[0099] The polished object polished by the method disclosed herein is typically washed after polishing. This washing can be performed using a suitable washing liquid. The washing liquid to be used is not particularly limited, and a known or commonly used one can be appropriately selected and used.

[0100] The polishing method disclosed herein may include any other steps in addition to the above-mentioned preliminary polishing step and finish polishing step. Such steps include a lapping step performed before the preliminary polishing step. The lapping step is a step of polishing the object to be polished by pressing the surface of a polishing platen, for example a cast iron platen, against the object to be polished. Therefore, a polishing pad is not used in the lapping step. The lapping step is typically performed by supplying abrasive grains between the polishing platen and the object to be polished. The abrasive grains are typically diamond abrasive grains. The polishing method disclosed herein may also include an additional step before the preliminary polishing step or between the preliminary polishing step and the finish polishing step. The additional step is, for example, a cleaning step or a polishing step.

[0101] <Method of manufacturing polished object> The technology disclosed herein may include a method for manufacturing an abrasive, which includes a polishing step using any of the polishing methods described above, and a method for providing an abrasive manufactured by the method. The method for manufacturing an abrasive is, for example, a method for manufacturing a silicon carbide substrate. That is, the technology disclosed herein provides a method for manufacturing an abrasive, which includes polishing an object to be polished made of a material to be polished by applying any of the polishing methods disclosed herein, and a method for manufacturing an abrasive manufactured by the method. The manufacturing method can efficiently provide an abrasive with improved surface quality, such as a silicon carbide substrate. EXAMPLES

[0102] Some examples of the present invention will be described below, but it is not intended that the present invention be limited to those shown in these examples. In the following description, "%" is based on weight unless otherwise specified.

[0103] The anionic polymers used in the following examples are as follows: Polymer A1: Polystyrene sulfonate sodium salt (manufactured by Tosoh Organic Chemical Co., Ltd., trade name "Polynas (registered trademark) PS-1", Mw 10000) Polymer A2: Polystyrene sulfonate sodium salt (manufactured by Tosoh Organic Chemical Co., Ltd., trade name "Polynas (registered trademark) PS-5", Mw 50000) Polymer B: Polyacrylic acid sodium salt (manufactured by Toagosei Co., Ltd., product name "A-210", Mw 3000) Polymer C: acrylic acid / 2-acrylamide 2-methylpropanesulfonic acid copolymer sodium salt (Mw 10000) The Mw of the above polymers is the nominal value given by the manufacturer.

[0104] <Test Example 1> <Preparation of Polishing Composition> Example 1 Alumina abrasive grains, potassium permanganate (KMnO4) as an oxidizing agent, anionic polymer, and deionized water were mixed to prepare the polishing composition of this example. The content of alumina abrasive grains was 6%, the content of potassium permanganate was 0.079 mol / L, and the content of anionic polymer was 0.08 g / L. The pH of the polishing composition was adjusted to the value shown in Table 1 using nitric acid and / or potassium hydroxide (KOH). As the alumina abrasive grains, α-alumina abrasive grains with a BET diameter of 0.5 μm were used. The BET diameter of the abrasive grains was measured using a surface area measuring device (product name "Flow Sorb II 2300") manufactured by Micromeritics. As the anionic polymer, polystyrene sulfonate sodium salt (polymer A2) with Mw of 50,000 was used.

[0105] (Examples 2 and 3) The polishing composition of this example was prepared in the same manner as in Example 1, except that the type and content of the anionic polymer were as shown in Table 1.

[0106] Comparative Example 1 The polishing composition of this example was prepared in the same manner as in Example 1, except that no anionic polymer was used.

[0107] Example 4 The polishing composition of this example was prepared in the same manner as in Example 1, except that sodium polystyrene sulfonate (Polymer A1) having a Mw of 10,000 was used as the anionic polymer and the pH of the polishing composition was adjusted to the value shown in Table 1 using nitric acid and / or KOH.

[0108] (Examples 5 to 7) The polishing composition of this example was prepared in the same manner as in Example 4, except that the type and content of the anionic polymer were as shown in Table 1.

[0109] Comparative Example 2 The polishing composition of this example was prepared in the same manner as in Example 4, except that no anionic polymer was used.

[0110] Example 8 The polishing composition of this example was prepared in the same manner as in Example 1, except that the pH of the polishing composition was adjusted to a value shown in Table 1 using nitric acid and / or KOH.

[0111] Comparative Example 3 The polishing composition of this example was prepared in the same manner as in Example 8, except that no anionic polymer was used.

[0112] (Examples 9 to 15) The polishing composition of this example was prepared in the same manner as in Example 1, except that the type and content of the anionic polymer were as shown in Table 2.

[0113] (Zeta potential measurement) The zeta potential [mV] of each polishing composition was measured using a high-concentration zeta potential meter (ZetaProbe) manufactured by Colloidal Dynamics, Inc. at a liquid temperature of 20 to 25° C. The absolute values ​​of the obtained values ​​are shown in the “Absolute Zeta Potential Value” column of Tables 1 and 2.

[0114] (Measurement of redox potential) For each polishing composition, the oxidation-reduction potential ORP [mV] relative to a standard hydrogen electrode was measured using an oxidation-reduction potentiometer (main body type: F-52, electrode type: 9300) manufactured by Horiba, Ltd., at a liquid temperature of 20 to 25° C. The measurement results are shown in the “ORP” column of Tables 1 and 2.

[0115] (Measurement of electrical conductivity) The electrical conductivity [mS / cm] of each polishing composition was measured using a Horiba Ltd. electrical conductivity meter (model "DS-71", electrode used "3552-10D") at a liquid temperature of 20 to 25° C. The measurement results are shown in the "Electrical Conductivity" column of Tables 1 and 2.

[0116] <Preliminary polishing of the object to be polished> A preliminary polishing composition was prepared containing alumina abrasive grains (6% by weight) with a BET diameter of 0.5 μm and permanganic acid (0.105 mol / L) as an oxidizing agent, with a pH adjuster added so that the pH was 8 to 10. Then, using the preliminary polishing composition, preliminary polishing was performed on a SiC wafer until the following surface quality was achieved. The preliminary polishing conditions were the same as the polishing conditions in <Polishing of the object to be polished> below. The pre-polishing was carried out so that the surface quality after the pre-polishing was such that the surface roughness Ra measured by an atomic force microscope (model: Nanoscope V) manufactured by Bruker was 0.07 nm or less.

[0117] <Polishing the object to be polished> The polishing surface of the object to be polished after the above-mentioned preliminary polishing was polished under the following polishing conditions using the polishing composition of each example as it is as a polishing liquid. [Policing conditions] Polishing equipment: Fujikoshi Machinery Co., Ltd., model "RDP-500" Polishing pad: Nitta Haas "SUBA800XY" Polishing pressure: 29.4kPa Polishing fluid supply rate: 20mL / min Plate rotation speed: 100 rpm Head rotation speed: 100 rpm Polishing time: 1 hour Polishing target: SiC wafer (conductivity type: n-type, crystal type 4H-SiC, off-angle of the main surface (0001) to the C-axis: 4°), 2 inches, 1 piece / batch Polishing solution temperature: 23℃

[0118] <Evaluation of polishing speed> The polishing composition according to each example was used as it was as a polishing liquid to carry out polishing under the above-mentioned polishing conditions, and the removal rate was calculated according to the following calculation formulas (1) and (2). (1) Polishing stock removal [cm] = Difference in weight of SiC wafer before and after polishing [g] / SiC density [g / cm 3 ](=3.21g / cm 3 ) / polished area [cm 2 ](=19.62cm 2 ) (2) Polishing speed [nm / h] = Polishing stock removal [cm] × 10 7 / Polishing time (=1 hour) The obtained values ​​were converted into relative values, with the value of the comparative example showing a pH in the same range as the pH of the polishing composition used being taken as 100%, and are shown in the "Relative Polishing Rate" column in Tables 1 and 2.

[0119] <Evaluation of friction coefficient> The polishing composition according to each example was used as a polishing liquid as it was, and the friction coefficient was measured when polishing was performed under the above-mentioned polishing conditions. When measuring the friction coefficient, a template using a suede backing material as a wafer holding part was used, and the wafer was attached so that the protrusion height was 200 μm or more. During polishing, the wafer was kept in a water-filled state against the suede material. The friction coefficient was directly adopted as the value output from the above-mentioned polishing device. The values ​​obtained here were converted into relative values, with the value of the comparative example, which showed a pH in the same range as the pH of the polishing composition used, set at 100%, and are shown in the ``Relative friction coefficient'' column in Tables 1 and 2.

[0120] [Table 1]

[0121] [Table 2]

[0122] As shown in Table 1, the polishing compositions of Examples 1 to 8 containing alumina abrasive grains, an oxidizing agent, and an anionic polymer exhibited a significantly reduced friction coefficient while maintaining the same or higher polishing rate compared to Comparative Examples 1, 2, and 3, which did not contain an anionic polymer and had a pH in the same range as each Example. Furthermore, as shown in Table 2, even when the content of the anionic polymer in the polishing composition was increased, a high friction reduction effect was observed while maintaining a good polishing rate.

[0123] <Test Example 2> <Preparation of Polishing Composition> (Example 16) The polishing composition of this example was prepared by mixing silica abrasive grains, hydrogen peroxide (H2O2) and sodium metavanadate (NaVO3) as oxidizing agents, anionic polymer, and deionized water. The content of silica abrasive grains was 29%, the content of H2O2 was 0.405 mol / L, the content of NaVO3 was 0.196 mol / L, and the content of anionic polymer was 0.32 g / L. The pH of the polishing composition was adjusted to the values ​​shown in Table 3 using nitric acid and / or potassium hydroxide (KOH). As the silica abrasive grains, colloidal silica with a BET diameter of 72 nm was used. The BET diameter of the abrasive grains was measured using a surface area measuring device (product name "Flow Sorb II 2300") manufactured by Micromeritics. As the anionic polymer, acrylic acid / 2-acrylamide 2-methylpropanesulfonic acid copolymer sodium salt (polymer C) with Mw of 10,000 was used.

[0124] (Example 17) The polishing composition of this example was prepared in the same manner as in Example 16, except that the content of the anionic polymer was as shown in Table 3.

[0125] Comparative Example 4 The polishing composition of this example was prepared in the same manner as in Example 16, except that no anionic polymer was used.

[0126] <Preliminary polishing of the object to be polished> A preliminary polishing composition was prepared containing alumina abrasive grains (6% by weight) with a BET diameter of 0.5 μm and permanganic acid (0.105 mol / L) as an oxidizing agent, with a pH adjuster added so that the pH was 8 to 10. Then, using the preliminary polishing composition, preliminary polishing was performed on a SiC wafer until the following surface quality was achieved. The preliminary polishing conditions were the same as the polishing conditions in <Polishing of the object to be polished> below. The pre-polishing was carried out so that the surface quality after the pre-polishing was such that the surface roughness Ra measured by an atomic force microscope (model: Nanoscope V) manufactured by Bruker was 0.07 nm or less.

[0127] <Polishing the object to be polished> The polishing surface of the object to be polished after the above-mentioned preliminary polishing was polished under the following polishing conditions using the polishing composition of each example as it is as a polishing liquid. [Policing conditions] Polishing equipment: Fujikoshi Machinery Co., Ltd., model "RDP-500" Polishing pad: Nitta Haas "SUBA800XY" Polishing pressure: 29.4kPa Polishing fluid supply rate: 20mL / min Plate rotation speed: 100 rpm Head rotation speed: 100 rpm Polishing time: 1 hour Polishing target: SiC wafer (conductivity type: n-type, crystal type 4H-SiC, off-angle of the main surface (0001) to the C-axis: 4°), 2 inches, 1 piece / batch Polishing solution temperature: 23℃

[0128] <Evaluation of polishing speed> The polishing composition according to each example was used as it was as a polishing liquid, and polishing was carried out under the above-mentioned polishing conditions. Then, similarly to the above-mentioned Test Example 1, the polishing rate was calculated according to the calculation formulas (1) and (2). The obtained value was converted into a relative value, with the value of the comparative example showing the same pH range as the pH of the polishing composition used being taken as 100%, and shown in the column of "relative polishing rate" in Table 3.

[0129] <Evaluation of friction coefficient> The polishing composition according to each example was used as it is as a polishing liquid, and the friction coefficient was measured when polishing was performed under the above-mentioned polishing conditions. The friction coefficient was measured in the same manner as in Test Example 1 described above. The obtained value was converted into a relative value, with the value of the comparative example showing the same pH range as the pH of the polishing composition used being taken as 100%, and is shown in the column of "relative friction coefficient" in Table 3.

[0130] [Table 3]

[0131] As shown in Table 3, the polishing compositions of Examples 16 and 17, which contained silica abrasive grains, an oxidizing agent, and an anionic polymer, had a significantly reduced friction coefficient while maintaining the same or higher removal rate as Comparative Example 4, which did not contain an anionic polymer and had a pH in the same range as each of the examples.

[0132] Although the specific examples of the present invention have been described in detail above, these are merely examples and do not limit the scope of the claims. The technology described in the claims includes various modifications and changes of the specific examples exemplified above.

Claims

1. A polishing composition used for polishing a surface composed of either silicon carbide or gallium nitride, comprising: The invention comprises water, an abrasive grain, and a composite metal oxide as an oxidizing agent, further comprising an anionic polymer, The anionic polymer is A homopolymer or copolymer containing at least one type of structural unit derived from styrenesulfonic acid, isoprene sulfonic acid, vinylsulfonic acid, allylsulfonic acid, isoamylenesulfonic acid, 2-(meth)acrylamide-2-methylpropanesulfonic acid, or methallylsulfonic acid in one molecule, and a homopolymer comprising a structural unit derived from sulfonic acid; or a copolymer comprising a structural unit derived from sulfonic acid, a structural unit derived from (meth)acrylic acid, and a structural unit derived from acrylamide; The content of the anionic polymer is 0.05 g / L or more and 1.0 g / L or less, A polishing composition comprising a permanganate as the composite metal oxide.

2. The polishing composition according to claim 1 , having a pH of 2.5 or more and 9.0 or less.

3. The method includes the step of polishing an object to be polished using the polishing composition according to claim 1 or 2, A polishing method, wherein the object to be polished is a surface made of either silicon carbide or gallium nitride.

Citation Information

Patent Citations

  • Chemical-mechanical abrasive material composition used for semiconductor process

    JP2000049124A

  • Polishing solution for copper and polishing method

    JP2006086353A

  • Polishing solution for metal

    JP2009295747A

  • Polishing liquid composition

    JP2012135863A

  • Composition for polishing, method for polishing substrate for magnetic disk using the same, and method for manufacturing substrate for magnetic disk using the polishing method

    JP2017182849A